Preparing method of 2-substituted benzoxazole compounds - XING RUIGUANG; WANG BO; LI YA'NAN (2015)
The invention relates to a preparing method of 2-substituted benzoxazole compounds. The compounds are obtained by reaction of products obtained by reaction of acyl chloride and o-nitrophenol or derivatives thereof under catalyzing of reducing agent ammonium formate, a solvent and palladium-containing agents. According to the method, the reaction condition is mild, environment is protected, raw materials are rich and easy to obtain, operation is easy, yield is high, and various kinds of performance are optimized.